Utilization of information technology in implementation active learning in private vocational school, PTPN 4 private vocational school Dolok Ilir in dealing with industrial revolution 4.0 era - Tulus; Marpaung, Tulus Joseph Herianto; Sawaluddin; Syahputra, Muhammad Romi; Zarlis, Muhammad (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
After the millennium era, the development of information technology (IT) was sufficient quickly, changes in business patterns have also increased sharply. This is called the disruption era. IT technology has also penetrated the world of Education, both in management too learning method. In the world of education now the learning method is not only using conventional methods such as from textbooks and explanations from teachers only, but also with effective learning methods and efficiently by utilizing information technology. An example is the media multimedia based learning. Community service is wrong one way that can be used to carry out information technology correctional. Community service that will be carried out in this study is entitled Utilization of Information Technology in the Implementation of Active Learning in Schools PTPN4 Dolok Ilir Private Middle School In the Face of the Industrial Revolution Era 4.0, with the aim of helping teachers in the process of learning mathematics more interesting interactive and fun, because in general middle school students The first has many uses of telecommunications equipment that is equipped with various kinds of multimedia. The result of this service learning media will be made mathematics that includes the problem of building and space in accordance with the curriculum Junior high school.